Ethical ladder 2.0 / Asmidar Lokman … [et al.] - Lokman, Asmidar; Ab. Rahman, Farah Adilla; Mohd Shazali, Nurliyana; Ahmad, Nasyrah; Haris, Siti Melinda (Division of Research and Industry Linkages, 2017)
This educational game aims to assist the students in understanding the content of ADS452 (Ethics in Administration). The findings of the survey revealed that majority of the students who played the game understood the basic concept of ethics. This indicates that this game is able to enhance the students’ knowledge on ethics. In sum, this board game is an interactive way in teaching and learning process. It helps to improve their understanding of the course. This game also serves as an assessment alternative, encourages healthy competition and promotes teamwork among students. It has the potential to be used across disciplines and educational levels.